Dilemmas and Coping Strategies of Chinese International Students’ Mental Health Problems: The Parents’ Perspectives - Jin, Lan; Acharya, Lalatendu (Journal of International Students, 2021)
Talking about mental health issues like depression with parents is a challenging exercise for Chinese international students (CISs) as well as their parents due to their cultural context and family hierarchical structure. This study engages with the parents of CISs to identify their dilemmas and coping strategies employed to discuss depression with their children studying in United States. Thirteen Chinese parents of CISs were recruited into in-depth interviews. A constant comparative method was employed for data analysis. The results revealed that the parents struggled with different dilemmas while talking about depression. Four coping strategies emerged: (a) communicating openly, (b) improving understanding through social media and shared experiences, (c) respecting, being sensitive, and not being judgmental, and (d) encouraging help-seeking and support-seeking. The findings provide crucial insights for mental health interventions involving parents of CISs.